2011
DOI: 10.1021/mp2002973
|View full text |Cite
|
Sign up to set email alerts
|

Coamorphous Drug Systems: Enhanced Physical Stability and Dissolution Rate of Indomethacin and Naproxen

Abstract: One of the challenges in drug development today is that many new drug candidates are poorly water-soluble, and one of the approaches to overcome this problem is to transfer a crystalline drug into its amorphous form, thus increasing dissolution rate and apparent solubility of the compound. In this study, a coamorphous drug/drug combination between the two nonsteroidal anti-inflammatory drugs, naproxen and γ-indomethacin, was prepared and investigated. At molar ratios of 2:1, 1:1 and 1:2, the drugs were quench … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
229
4
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 314 publications
(250 citation statements)
references
References 34 publications
(69 reference statements)
13
229
4
2
Order By: Relevance
“…These results indicated that the COAD used to prepare the films greatly enhanced the extent and rate of dissolution of OL from the prepared OFDF. This enhancement was a result of the synchronized dissolution of OL and ascorbic acid brought about by the co-amorphous dispersion (Löbmann et al, 2011). The cumulative percentage of drug released after 10 min (Q 10min ) was evaluated among different films.…”
Section: Assessment Of In Vitro Disintegration and Dissolution Of Thementioning
confidence: 99%
“…These results indicated that the COAD used to prepare the films greatly enhanced the extent and rate of dissolution of OL from the prepared OFDF. This enhancement was a result of the synchronized dissolution of OL and ascorbic acid brought about by the co-amorphous dispersion (Löbmann et al, 2011). The cumulative percentage of drug released after 10 min (Q 10min ) was evaluated among different films.…”
Section: Assessment Of In Vitro Disintegration and Dissolution Of Thementioning
confidence: 99%
“…By the definition of Dengale et al, these systems contain two or more small molecular weight compounds that are homogenously mixed to form an amorphous single phase system [19]. For example, two active compounds have been combined to produce co-amorphous mixtures [20,21], but finding compatible drug-drug pairs may, however, be challenging, which has increased the interest in combining a pharmacologically active molecule with an inactive low molecular weight excipient, such as an amino acid (AA) [22][23][24].…”
mentioning
confidence: 99%
“…These systems show molecular interaction between two components (17) or without evidence of intermolecular interactions (13). In this investigation, ATC in the presence of NIC was completely converted to the coamorphous form, as it is evident from disappearance of typical pattern of ATC in PXRD and melting endotherm in DSC thermogram (32)(33).…”
Section: Disscussionmentioning
confidence: 61%
“…Amorphous small molecule mixtures (coamorphous or amorphous cocrystals) is an example of one such recent method developed to produce amorphous drugs in the presence of a second compound which could either be another active pharmaceutical agent or an excipient, resulting in improved stability (10). Cimitidineindomethacin (11), ranitidine hydrochlorideindomethacin (12), simvastatin-glipizide (13), cimetidine-diflunisal (14), acyclovir-citric acid (15), naproxen-cimetidine (16) and indomethacinnaproxen (17) are examples of coamorphous systems from the literature.…”
Section: Introductionmentioning
confidence: 99%